Efektivitas Kinerja Lembaga Ombudsman RI Perwakilan Sumatera Barat dalam Menangani Maladministrasi Pelayanan Publik - Najmy, Rain; Hudmi; Syafril, Rizki (Jurnal Ilmu Manajemen, Bisnis dan Ekonomi, 2024)
Reports about maladministration in Indonesia continue to increase. This caused the government to form an institution called the Ombudsman to receive and handle maladministration problems that often occur in the government. The main problem is how effectively the Indonesian Ombudsman Representative for West Sumatra handles the problem of maladministration of public services. Data collected through qualitative descriptive methods using observation, interviews and documentation. Primary and secondary data are the data sources used. The research results show that the Indonesian Ombudsman Representative for West Sumatra has fulfilled the four effectiveness criteria. Thus, this institution can be considered quite effective in handling public service maladministration according to procedures and continues to try to resolve maladministration complaints according to targets even though there are shortages in staff or employees.